86 Achievement of blood pressure, lipids and glucose targets in patients with coronary disease or at high risk of developing atherosclerotic cardiovascular disease in europe: results from euroaspire survey. (5th June 2017) - Kotseva, Kornelia; Wood, David; Jennings, Catriona; Bacquer, Dirk De; Backer, Guy De
Abstract : Introduction: EUROASPIRE IV is a cross-sectional survey undertaken in 26 European countries to evaluate the implementation of the Joint European Societies guidelines on cardiovascular (CVD) prevention in everyday clinical practice. Methods: Patients <80 years with 1) coronary disease or 2) identified as high CVD risk on the basis of being on blood pressure and/or lipid-lowering medication and/or having diabetes, were interviewed at least six months after the recruiting coronary event or the start of medication.using standardised methods and instruments. Results: A total of 7998 coronary patients (24% females) and 4579 high CVD risk individuals (59% women) were interviewed. The risk factor control was poor in both groups. Among those on blood pressure lowering medication the target of <140/90/90 mm Hg (<140/80/80 mm Hg in people with diabetes) was achieved by 53% of coronary patients and 43% of high CVD risk individuals. Only 21% of coronary patients attained the LDL-cholesterol goal of <1.8 mmol/L and 33% of high CVD risk individuals achieved the target of <2.5 mmol/L. Among people treated for type 2 diabetes mellitus, 53% of coronary patients and 59% of high CVD risk individuals achieved the glycated haemoglobin (HbA1c) target of <7.0%. Compared with data from previous surveys the control of blood pressure and LDL-cholesterol in coronary patients improved significantly. There was a trend in improving of blood pressure and lipids management in patients at high CVD risk. In both groups, glycaemic control in patients with previously known diabetes was similar to that observed in the third survey. Conclusion: Despite advances in patient management there is further potential to improve risk factor control in patients with coronary disease and those at high risk of developing CVD. Although the risk factors studied were better controlled than in previous surveys, there is still considerable potential to further reduce cardiovascular risk through lifestyle and optimised cardioprotective medications. A significant gap continues to exist between the prevention guidelines and their adherence in everyday clinical practice in Europe.